Evaluating the Financial Performance Through Consumer Centric Decision Approach in Pharmaceutical Companies of Bangladesh: a Business Planning Perspective - Zaman, Mahmud Uz; Pritha, Sabiha Afroz; Rahman, Md Mostafizur (European Journal of Economics and Business Studies, 2022)
Pharmaceuticals agglomerations consistently use their brand image and versatile product portfolios to consolidate their position in the financial sector, which is evident in their continuous profit making and expansion in market share. This paper explores the short-term and long-term investment attractiveness through ‘consumer centric decision approach in two selected pharmaceutical companies, Renata Limited and Orion Pharma Limited, of Bangladesh over the last three years period. This research adopts a systematic approach which primarily addresses the various concerns of investors to illustrate the decision-making process of the existing and future investors. Using primarily domestic transaction data, this study explores how the leading pharmaceuticals companies of Bangladesh effectively use the wide array of drug portfolios mix with appropriate branding techniques to increase their financial profit and market share simultaneously. Both SWOT analysis and Porters Five Forces Model explore the business analysis of Renata Limited in compare to Orion Pharma Limited that provides a conclusion regarding investors decision to invest in Renata Limited. Considering the financial analysis, Renata s financial liquidity is not very satisfactory and could have been improved further if management is prudent on financial strategy settings. Findings of the business analysis indicate that Renata Limited would be a good investment choice for existing and prospective shareholders based on its opportunities for long term and short term growth and further expansion in developing the market. The results suggest that even lower liquidity coupled with higher interest borrowings can be balanced by posing positive picture to the public shareholders by returning the positive dividend to them.
Keywords: Financial performance, ‘Consumer Centric Decision’ approach, Business Planning